Comprehensive inventory of páramo birds and their habitat affinities in a conservation hotspot, the Macizo del Cajas Biosphere Reserve, southern Ecuador - Pedro X. Astudillo; Santiago Barros; Fernando R. Villegas; David C. Siddons; Steven C. Latta (Revista Peruana de Biología)
The páramo ecosystem is a significant centre of Andean bird diversity with high concentrations of threatened species. The Macizo del Cajas Biosphere Reserve’s páramos are a district of the biogeographic páramo province of northern Andes and are therefore considered a conservation hotspot with representative bird diversity. To enhance regional conservation efforts, comprehensive inventories of bird species that occupy this páramo are required. We present an updated bird inventory for the páramos of Macizo del Cajas and included validated records from eBird and GBIF databases along with records from continuous monitoring across this páramo landscape for five years. We also provide notes on habitat affinity and important new, rare, restricted range, and threatened birds. We report 112 bird species within the reserve, including five endemics, and three globally and 12 nationally threatened species. Finally, we discuss the use of habitat affinities as indicators of biodiversity patterns in páramo to improve conservation tools for key habitats.